Antioxidant Defense, Redox Homeostasis, and Oxidative Damage in Children With Ataxia Telangiectasia and Nijmegen Breakage Syndrome - Maciejczyk, Mateusz; Heropolitanska-Pliszka, Edyta; Pietrucha, Barbara; Sawicka-Powierza, Jolanta; Bernatowska, Ewa; Wolska-Kusnierz, Beata; Pac, Małgorzata; Car, Halina; Zalewska, Anna; Mikoluc, Bozena (Frontiers in Immunology, 2019)
Ataxia-telangiectasia (AT) and Nijmegen breakage syndrome (NBS) belong to a group of primary immunodeficiency diseases (PI) characterised by premature aging, cerebral degeneration, immunoglobulin deficiency and higher cancer susceptibility. Despite the fact that oxidative stress has been demonstrated in vitro and in animal models of AT and NBS, the involvement of redox homeostasis disorders is still unclear in the in vivo phenotype of AT and NBS patients. Our study is the first to compare both enzymatic and non-enzymatic antioxidants as well as oxidative damage between AT and NBS subjects. Twenty two Caucasian children with AT and twelve patients with NBS were studied. Enzymatic and non-enzymatic antioxidants – glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase-1 (SOD) and uric acid (UA); redox status – total antioxidant capacity (TAC) and ferric reducing ability of plasma (FRAP); and oxidative damage products – 8-hydroxy-2’-deoxyguanosine (8-OHdG), advanced glycation end products (AGE), advanced oxidation protein products (AOPP), 4-hydroxynonenal (4-HNE) protein adducts, and 8-isoprostanes (8-isop) were evaluated in serum or plasma samples. We showed that CAT, SOD and UA were significantly increased, while TAC and FRAP levels were statistically lower in the plasma of AT patients compared to controls. In NBS patients, only CAT activity was significantly elevated, while TAC was significantly decreased as compared to healthy children. We also showed higher oxidative damage to DNA (↑8-OHdG), proteins (↑AGE, ↑AOPP) and lipids (↑4-HNE, ↑8-isop) in both AT and NBS patients. Interestingly, we did not demonstrate any significant differences in the antioxidant defence and oxidative damage between AT and NBS patients. However, in AT children, we showed a positive correlation between 8-OHdG and the -fetoprotein level as well as a negative correlation between 8-OHdG and IgA. In NBS, AGE was positively correlated with IgM and negatively with the IgG level. Summarising, we demonstrated an imbalance in cellular redox homeostasis and higher oxidative damage in AT and NBS patients. Despite an increase in the activity/concentration of some antioxidants, the total antioxidant capacity is overwhelmed in children with AT and NBS and predisposes them to more considerable oxidative damage. Oxidative stress may play a major role in AT and NBS phenotype.